Rancang Bangun Aplikasi Presensi Online Menggunakan QR Code Scanner dan Lokasi Berbasis Android - Tarsinah Sumarni; Raka Putra Pratama (TeknoIS : Jurnal Ilmiah Teknologi Informasi dan Sains, 2023)
AMIK HASS Bandung is a private university engaged in D3 education with an Informatics Management study program. AMIK HASS Bandung has many activities in each of his learning activities, one of which is the attendance process. The attendance data collection process is carried out by filling out and collecting documents that have been filled out by students or employees so that the data recording process is still a bit long, it is necessary to have an application that helps the data management process more effectively and report results quickly, precisely and accurately. In the preparation of this final report, there are several methods of analyzing, namely Class Diagrams, and prototypes. In addition, the author also uses data collection techniques in the form of observations related to this research and the software used is PHP, Java, Android Studio and MySQL